2016
DOI: 10.18632/oncotarget.11917
|View full text |Cite
|
Sign up to set email alerts
|

Heme oxygenase-1 deficiency exacerbates angiotensin II-induced aortic aneurysm in mice

Abstract: Abdominal aortic aneurysm (AAA) is a chronic but often fatal disease in elderly population. Heme oxygenase-1 (HO-1) is a stress response protein with antioxidative and anti-inflammatory properties. HO-1 has been shown to protect against atherogenesis and arterial intimal thickening. Emerging evidences suggest that AAA and arterial occlusive disease have distinct pathogenic mechanisms. Thus, in this study we investigated the role of HO-1 in angiotensin II-induced AAA formation in HO-1+/+apoE−/− and HO-1−/−apoE−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 39 publications
3
37
0
Order By: Relevance
“…Its reactive products have potent anti-inflammatory and anti-oxidative functions. Shaw-Fang Yet et al demonstrated that a deficiency in HO-1 exacerbates angiotensin II-induced aortic aneurysm in mice (Ho et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Its reactive products have potent anti-inflammatory and anti-oxidative functions. Shaw-Fang Yet et al demonstrated that a deficiency in HO-1 exacerbates angiotensin II-induced aortic aneurysm in mice (Ho et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…To detect renal ROS production, an in situ dihydroethidium (DHE, Sigma-Aldrich, USA) fluorescence was performed [ 19 ]. Kidney frozen sections (5 μ m) were incubated with 1 μ mol/l DHE at 37°C in a light-protected, humidified chamber at room temperature for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, catalase overexpression in aortic smooth muscle cells prevented pathological mechanical changes underlying AAA formation [ 168 , 169 ]. In addition, hemoxygenase-1 deficiency aggravates Angiotesin-II induced aortic aneurysms in the ApoE −/− model [ 170 ].…”
Section: Antioxidants As a Potential Therapeutic Strategy To Prevementioning
confidence: 99%